Design of Particle Morphology for Redox‐Initiated Spray Polymerization of Acrylic Acid and Sodium Acrylate by Investigating Levitated Single Droplet. Issue 1 (23rd December 2016) - Wong, Doris; Hellwig, Thomas; Halfar, Annelie H.; Moritz, Hans‐Ulrich; Pauer, Werner
Summary: In order to optimize the spray polymerization of acrylic acid and sodium acrylate, an acoustic levitator was efficiently utilized to model the system. The acoustic levitator simulates the fall of a droplet in a spray tower. A particle morphology map of SEM images was designed to reproduce certain particle surfaces by varying the drying conditions and the initiator system, which were adjusted for a polymerization. Thus, a droplet of an aqueous monomer mixture of acrylic acid and sodium acrylate was positioned in an acoustic levitator and the polymerizations were initiated with two redox systems, one with ammonium peroxodisulfate and the other one with potassium peroxodisulfate, and were compared to each other. The redox system can beneficially initiate the polymerization at low temperature (>40 °C). By means of a camera and a light source, shadowgraphy was used to analyze the droplet drying kinetics.